Ujian dalam Menghadapi Bencana Gempa Bumi Berdasarkan Pengalaman Masyarakat Muslim di Lahad Datu, Sabah - Suraya Sintang; Assis Kamu; Baba Musta (UTM Press, 2022)
Natural disasters are an unavoidable nature, and this phenomenon has been proven to occur either from a religious or scientific perspective. From the Islamic point of view, natural disasters considered as test of faithfulness. This study endevours to conceptualise the meaning of trial and its relation to the understanding of the Muslim community in Lahad Datu. The study discusses action taken by them in facing this natural disaster. This study employed quantitative method through distributing questionnaires around the district of Lahad Datu. The descriptive analysis was done to analyse the relationship between the demographic background of Muslim respondents with their level of understanding and knowledge of earthquake as a test of God. The results showed that majority of respondents, 80 percent, had experienced an earthquake. The average knowledge of the respondents about the history of the earthquake in Lahad Datu is at a minimum level and it can be said that the knowledge about the earthquake is based on the current or latest knowledge that they have experienced themselves. Nevertheless, respondents had a basic knowledge of earthquake as shown on the physical actions they took after an earthquake such as being aware of increasing the level of family safety and participating in disaster awareness programs. The results also show the respondents’ belief that the earthquake is a test of God can be true because their actions and practices after the earthquake are more towards positive practices that are not contrary to Islamic teachings. The study concludes that a holistic approach through the integration of science (geology) and religion (Islam) should be highlighted as a method for improving disaster risk reduction management in Malaysia, especially victims involving the Muslim community.